The Mating Pattern of Captive Naked Mole-Rats Is Best Described by a Monogamy Model - Szafranski, Karol; Wetzel, Michaela; Holtze, Susanne; Büntjen, Ina; Lieckfeldt, Dietmar; Ludwig, Arne; Huse, Klaus; Platzer, Matthias; Hildebrandt, Thomas (Frontiers in Ecology and Evolution, 2022)
Naked mole-rats form colonies with a single reproductively active female surrounded by subordinate workers. Workers perform offspring care, construction and defense of the burrow system, and food supply. Such division of labor, called 'cooperative breeding', is strongly associated with the evolution of monogamous mating behavior, as seen in several mammalian lineages. This association is explained by the evolutionary theory of kin selection, according to which a subordinate adult may help to raise other's offspring if they are in full sibling relationship. In conflict with this theory, the naked mole-rat is widely considered to be polyandrous, based on reports on multiple males contributing to a colony’s progeny. In order to resolve this contrast, we undertook an in-depth microsatellite-based kinship analysis on captive colonies. Four independent colonies comprising a total of 265 animals were genotyped using a panel of 73 newly established microsatellite markers. Our results show that each mole-rat colony contains a single monogamous breeder pair, which translates to a reproductive skew of 100% for both sexes. This finding, also in conjunction with previously published parental data, favors monogamy as the best-fitting model to describe naked mole-rat reproduction patterns. Polyandry or other polygamous reproduction models are disfavored and should be considered as exceptional. Overall, the empirical genetic data are in agreement with the kin selection theory.